2019
DOI: 10.3390/pathogens8040201
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Leishmanicidal Evaluation of Pulicaria Inuloides Root Extracts: A Bioguided Fractionation

Abstract: Leishmaniasis remains a major world health problem, and in particular, Algeria ranks second for the incidence of cutaneous leishmaniasis. Pulicaria inuloides is a well-known Arabian Peninsula medicinal plant. In the present study, the chloroform, ethyl acetate and n-butanol extracts from the roots of Pulicaria inuloides were analyzed for antioxidant activity and its correlation with the total phenolic and flavonoid contents. The highest antioxidant activity using a DPPH assay was showed by the ethyl acetate ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Previously, our work on P. inuloides root extracts [16] indicated that the highest antioxidant activity by DPPH assay was reported for the ethyl acetate extract (IC 50 = 4.08 µg/ mL) which also had the highest total phenol content (307.12 µgAGE). Furthermore, previously published results of Al-Hajj et al [18] showed a significant antioxidant activity by DPPH and β-carotene assays for P. inuloides extracts (81.0 and 72.2%, respectively) which had also the highest total phenol and flavonoid contents (91.2 mgAGE/g and 75.0 mgQE/g, respectively).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Previously, our work on P. inuloides root extracts [16] indicated that the highest antioxidant activity by DPPH assay was reported for the ethyl acetate extract (IC 50 = 4.08 µg/ mL) which also had the highest total phenol content (307.12 µgAGE). Furthermore, previously published results of Al-Hajj et al [18] showed a significant antioxidant activity by DPPH and β-carotene assays for P. inuloides extracts (81.0 and 72.2%, respectively) which had also the highest total phenol and flavonoid contents (91.2 mgAGE/g and 75.0 mgQE/g, respectively).…”
Section: Resultsmentioning
confidence: 87%
“…The DPPH (2,2-diphenyl-1-picrylhydrazyl) solution (0.04 mg/mL) was used to evaluate the antioxidant properties of extracts [16]. Samples were prepared at 5.0 mg/mL, then, 30 μL of sample solutions at different concentrations were added to 3.0 mL of the DPPH solution.…”
Section: Dpph Radical Scavenging Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The results of RP-HPLC-DAD analysis ( Figure 2 e) showed that 10-isobutyryloxy-8,9-epoxy-thymyl isobutyrate is a major terpenoid constituent of the plant roots. The compound has been recently described as an inhibitor of aberrant proliferative signaling in melanoma cells [ 38 ] and antileishmanial agent [ 39 ] and is known as a secondary metabolite synthesized by numerous species from the Asteraceae [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The flowers of the plant are used in Yemen as a spice [ 21 ]. Recently, the evaluation of the leishmanicidal potential of P. inuloides has led to the isolation of its active constituents: quercetagetin-3,5,7,3’-tetramethyl ether and 8,9-epoxy-10-isobutyryloxythymyl isobutyrate [ 22 , 23 ]. Data on the chemical composition of the plant are sparse.…”
Section: Introductionmentioning
confidence: 99%